Exclusive breast feeding: a cross sectional survey about knowledge, attitudes and practices among lactating mothers in Pilkhuwa, Hapur - Kumar, Pankaj (International Journal Of Community Medicine And Public Health, 2020)
Background: Exclusive breast feeding is a basic human activity, vital to infant and maternal health and of immense economic value to households and societies. Studies in India have also shown a decline in breastfeeding trends, especially in urban areas. The WHO recommends that for the first six months of life, infants should be exclusively breastfed to achieve optimal growth, development, and health. Thereafter, infants should receive nutritionally adequate and safe complementary foods, while continuing to breastfeed for up to two years or more. Thus the present study was developed to examine the infant feeding practices, knowledge and attitude towards breast feeding among postnatal mothers. Methods: This was a cross sectional study carried out among post natal mothers who attended immunization clinics with their children for vaccination and for the treatment of other minor illnesses at a UHTC (Urban Health Training Centre). Results: Sixty three percent mothers were aware about exclusive breast feeding. Hospital/health facilities were the main source of information. A significant decrease about misconceptions and significant increase in knowledge occurred about exclusive breast feeding, in post testing. Conclusions: Promotion of women’s education, husband’s engagement, encouraging antenatal care and exclusive breastfeeding counselling during antenatal care were recommended to improve exclusive breastfeeding practice.